2002
DOI: 10.1093/annonc/mdf318
|View full text |Cite
|
Sign up to set email alerts
|

The clinical value of nuclear medicine in the assessment of irradiation-induced and anthracycline-associated cardiac damage

Abstract: Two groups of patients, those treated for Hodgkin's disease and breast cancer, are particularly at risk of developing late myocardial damage, since radiotherapy (RT) techniques for both patient groups may include (large) parts of the heart, and adjuvant systemic therapy is frequently administered to these patients, in particular anthracycline-containing chemotherapy. Available literature on the monitoring and prediction of RT-induced and anthracycline-associated cardiac damage using nuclear medicine techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Their results were similiar to our findings. Many studies emphasize that LV diastolic dysfunction detected by MUGA may be an early evidence of anthracycline cardiotoxicity [3,5,20,32]. In the present study, similiar to Cottin et al [33], we found simultaneous drop in both systolic and diastolic functions with MUGA.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Their results were similiar to our findings. Many studies emphasize that LV diastolic dysfunction detected by MUGA may be an early evidence of anthracycline cardiotoxicity [3,5,20,32]. In the present study, similiar to Cottin et al [33], we found simultaneous drop in both systolic and diastolic functions with MUGA.…”
Section: Discussionsupporting
confidence: 88%
“…It is clear that cardiotoxicity will increase with higher cumulative doses [1,6,7,14]. Besides the cumulative dose mediastinal irradiation, young age at the time of treatment, preexisting heart disease, concomitant therapy with cyclophosphamide and other chemotherapeutic agents, high infusion rate of anthracycline, and female gender contribute to cardiotoxicity [1,3,14,20]. Although 3 patients in the study group had thoracic radiotherapy, doses were lower than cardiotoxic limit for irradiation [21].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A typical manifestation is the progressive reduction of the EF leading to dilatated or restrictive cardiomyopathy [6]. This manifestation is associated with worse prognosis because of decompensation, severe arrhythmias or valve damage [57,62,63].…”
Section: Anthracycline-induced Cardiac Side Effectsmentioning
confidence: 99%
“…Therefore, diagnosis of radiationinduced cardiomyopathy needs multimodality assessment using echocardiography, 2 cardiac MRI, 3 and myocardial perfusion imaging. 4 Late gadolinium enhancement has been detected in half of patients who received RTx for esophageal cancer. 3 The present patient did not develop myocardial fibrosis.…”
Section: Kawamura G Et Almentioning
confidence: 99%